JOLIET, CHARTER AND REVISED ORDINANCES, ch. 49, §§ 1-3 (News Steam Printing House 1884). - (:unkn) unknown (General Publisher, 1884)
All persons upon whom shall be found any gambling apparatus or device, or any slung shot, pistol or knuckler of lead, brass or other metal, or any instrument, composition or thing used for the commission of burglary, arson, or for the picking of locks or pockets, or for the playing of any fraudulent tricks, plays or games, or for the manufacture of counterfeit money, or for the commission of any offense against the laws of this state, or the ordinances of said city, and who cannot give a good and satisfactory account of their possession of the same.
--
Keywords: CARRY - INTENT TO COMMIT CRIME